The effect of the antibiotic stewardship program (ASP) on community-acquired pneumonia (CAP): a before–after study - Fésüs, Adina; Baluku, Phiona; Sipos, Éva; Somodi, Sándor; Berczi-Kun, Enikő; Lekli, István; Bácskay, Ildikó; Benkő, Ria; Vaskó, Attila (Frontiers in Pharmacology, 2024)
Background: Community-acquired pneumonia (CAP) is one of the leading causes of death worldwide. Antibiotic stewardship program (ASP) has been implemented to improve rational and responsible antibiotic use by encouraging guideline adherence. Objective: This retrospective observational before–after study aimed to evaluate whether the ASP may improve guideline adherence, antibiotic exposure, and clinical outcomes in patients hospitalized due to CAP in Hungary. Methods: The study was conducted at a pulmonology department of a tertiary care medical center in Hungary. The ASP implementation consisted of written and published guidelines available to all professionals, continuous supervision, and counseling services on antibiotic therapies at an individual level, with the aim of ensuring compliance with CAP guidelines. Overall guideline adherence (agent selection, route of administration, and dose), clinical outcomes (length of stay and 30-day mortality), antibiotic exposure, and direct costs were compared between the two periods. Fisher’s exact test and t-test were applied to compare categorical and continuous variables, respectively. P-values below 0.05 were defined as significant. Results: Significant improvement in overall CAP guideline adherence (30.2%), sequential therapy (10.5%), and a significant reduction in the total duration of antibiotic therapy (13.5%) were observed. Guideline non-adherent combination therapies with metronidazole decreased significantly by 28.1%. Antibiotic exposure decreased by 7.2%, leading to a significant decrease in direct costs (23.6%). Moreover, the ASP had benefits for clinical outcomes, and length of stay decreased by 13.5%. Conclusion: The ASP may play an important role in optimizing empirical antibiotic therapy in CAP having a sustained long-term effect.